2021
DOI: 10.1002/ana.26173
|View full text |Cite
|
Sign up to set email alerts
|

Subicular Caspase‐1 Contributes to Pharmacoresistance in Temporal Lobe Epilepsy

Abstract: Objective Unidentified mechanisms largely restrict the viability of effective therapies in pharmacoresistant epilepsy. Our previous study revealed that hyperactivity of the subiculum is crucial for the genesis of pharmacoresistance in temporal lobe epilepsy (TLE), but the underlying molecular mechanism is not clear. Methods Here, we examined the role of subicular caspase‐1, a key neural pro‐inflammatory enzyme, in pharmacoresistant TLE. Results We found that the expression of activated caspase‐1 in the subicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Using female Wistar rats as in Löscher's initial studies, Xu et al [86] reported that the expression of activated caspase-1 in the subiculum, but not the CA1, was upregulated in phenytoin-resistant amygdala-kindled rats. Genetic ablation of caspase-1 interfered with the genesis of pharmacoresistance in the kindling model.…”
Section: Cellular and Molecular Mechanisms Of Pharmacoresistance In A...mentioning
confidence: 99%
“…Using female Wistar rats as in Löscher's initial studies, Xu et al [86] reported that the expression of activated caspase-1 in the subiculum, but not the CA1, was upregulated in phenytoin-resistant amygdala-kindled rats. Genetic ablation of caspase-1 interfered with the genesis of pharmacoresistance in the kindling model.…”
Section: Cellular and Molecular Mechanisms Of Pharmacoresistance In A...mentioning
confidence: 99%
“…This is consistent with the findings of Galic et al and others ( Vezzani and Granata, 2005 ; Galic et al, 2008 ; D’Ambrosio et al, 2013 ), who found that anti-TNF-α monoclonal antibodies blocked the proepileptic effects of lipopolysaccharide; moreover, Choi et al (2009) demonstrated considerable elevation of pro-inflammatory cytokines such as IL-1β in brain tissue of epileptic patients in addition to TNF-α, but these phenomena did not occur in our experiments, which may be related to the regions of the examined brain tissues. In a recent study, elevated levels of IL-1β has also been considered to probably have brain region specificity in a TLE animal model ( Xu et al, 2021b ). Hence, we will further explore the changes of inflammatory factors in more brain regions in our subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, one-third of the PWEs cannot achieve desirable outcomes, which is diagnosed as pharmacoresistant epilepsy (Kwan and Brodie, 2000 ). Pharmacoresistant epilepsy usually shares more severe pathological conditions including hyperexcitable circuitry and abnormally activated molecular pathways (Xu et al, 2019 , 2021 ), resulting in the intractability of successful management. With increased clinical findings, it is somehow convincible that epilepsy with ATP1A3 mutation shares a high incidence of being pharmacoresistant.…”
Section: Clinical Evidence About Atp1a3 Alteration...mentioning
confidence: 99%